Enhanced Infrared Shielding Function in ATO-Doped Polymer-Dispersed Liquid Crystal Films - Hongren Chen; Baohua Yuan; Xiao Wang; Xiaoming Zhang; Qilei Wang; Zuowei Zhang; Yunxiao Ren; Yihai Yang; Zihui Ye; Ruochen Lan; Lanying Zhang; Wei Hu; et al. (Molecules)
The enhanced infrared shielding function of antimony tin oxide (ATO)-doped polymer-dispersed liquid crystal (PDLC) film enables its use for smart windows, because it can switch between transparent and scattered states, which can protect people’s privacy. When PDLC film is used for a building’s doors and windows or external walls, we hope that it can have a higher infrared shielding capability, in order to reduce the indoor temperature affected by solar irradiation, so as to reduce the energy consumption caused by refrigeration equipment. However, the infrared shielding capability of the existing PDLC is far from sufficient. In this work, modified ATO nanoparticles of different sizes were introduced into the PDLC system to improve its infrared shielding capability. It was found that when the ATO particle size is 20 nm and the doping content is 0.6 wt%, the modified PDLC sample provides optimal infrared shielding function while maintaining excellent electro-optical properties.